Agricultural Footprint Dynamics: Capturing the Influence of Renewable Energy, Urbanization, and Ecological Resources - Ismat Nasim; Furrukh Bashir; Muhammad Ramzan (iRASD Journal of Energy & Environment)
Agriculture, a cornerstone of economic prosperity, is both a contributor to and a recipient of climate change. This study investigates the factors driving the agricultural footprint, considering land use, water use, pollution, greenhouse gas emissions, energy use, renewable energy consumption, urbanization growth rate, and ecological footprint components (fishing grounds, grazing land). Using principal component analysis, the study calculated an agricultural footprint index, weighting these factors. The study further estimated the impact of renewable energy consumption, urbanization growth rate, and ecological footprint components on the agricultural footprint. The stability of the model was assessed using CUSUM and CUSUM of squares calculations. The findings reveal that while renewable energy consumption and urbanization growth rate exert pressure on the agricultural footprint, ecological footprint components like fishing grounds, grazing land, and cropland contribute positively. To enhance the agricultural footprint and mitigate its environmental impact, the study proposed a multi-pronged approach: financial incentives, educational programs, consumer awareness campaigns, and the development of regulations and standards for sustainable agricultural practices. By implementing these strategies, society can promote a more sustainable and resilient agricultural sector that contributes to both economic prosperity and environmental protection.